Community Perceptions of the Results of Musrenbang Implementation in Pasar Minggu District, South Jakarta Administrative City, DKI Jakarta Province - Eti Sumiati; Dahyar Daraba; Meltarini (Sean Institute, 2024)
esearch on public perceptions of the results of the implementation of musrenbang in Pasar Minggu District, South Jakarta Administrative City, DKI Jakarta Province. This research uses a qualitative descriptive method, data collection techniques are carried out through in-depth interview studies, observation and documentation, the data sources used by informants using purposive sampling techniques are selected according to the research objectives, they are selected on the basis of consideration because they are seen to have information, are involved in technical, masterful, and directly involved in the process to be able to explain and provide data.The results of the research show that the public's perception from the cognitive aspect, namely regarding the implementation of the musrenbang, the template for the musrenbang proposal and the realization of the results of the implementation of the musrenbang show quite well because socialization had previously been provided. Furthermore, the public's perception of the results of the implementation of the musrenbang from the affective aspect, namely related to the implementation of the musrenbang, the musrenbang proposal template and the realization of the results of the implementation of the musrenbang show an attitude of agreement, only that the proposal template has not fully accommodated the community's proposals, and finally the public's perception of the results of the implementation of the musrenbang from the conative aspect, namely Regarding the implementation of the Musrenbang, the Musrenbang proposal template and the realization of the results of the Musrenbang implementation showed a fairly good assessment, although there were some who were not satisfied. In order to realize the results of the implementation of musrenbang in Pasar Minggu District, South Jakarta Administrative City, it has not run optimally due to inhibiting factors, including limited budget, limited implementation time and lack of coordination between SKPDs, efforts are needed by all existing stakeholders to achieve community satisfaction with the results of musrenbang implementation.